2005
DOI: 10.1149/1.1833315
|View full text |Cite
|
Sign up to set email alerts
|

Preparation and Electrochemical Performance of Spinel-Type Compounds Li[sub 4]Al[sub y]Ti[sub 5−y]O[sub 12] (y=0, 0.10, 0.15, 0.25)

Abstract: Ti 5Ϫy O 12 (y ϭ 0.10, 0.15, 0.25͒ were synthesized via solid-state reaction using TiO 2 -rutile, Li 2 CO 3 , and Al 2 O 3 as starting reagents. The charge-discharge cycling of the cells showed that the electrochemical performance of Li 4 Ti 5 O 12 prepared from rutile-type TiO 2 by our laboratory was as good as that produced by anatase-type TiO 2 . However, Al 3ϩ doped Li 4 Al y Ti 5Ϫy O 12 (y ϭ 0.10, 0.15) exhibited a much better electrochemical performance in comparison with undoped Li 4 Ti 5 O 12 . Among t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
31
1

Year Published

2007
2007
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 52 publications
(33 citation statements)
references
References 16 publications
1
31
1
Order By: Relevance
“…It is interesting that the first discharge capacity of 221 mAh g À1 in this study far exceeded the reported value of 195 mAh g À1 by Huang et al [16] and the theoretical value of $175 mAh g…”
Section: Electrochemical Performancecontrasting
confidence: 65%
See 1 more Smart Citation
“…It is interesting that the first discharge capacity of 221 mAh g À1 in this study far exceeded the reported value of 195 mAh g À1 by Huang et al [16] and the theoretical value of $175 mAh g…”
Section: Electrochemical Performancecontrasting
confidence: 65%
“…Such a calcination temperature to obtain a phase-pure Al-Li 4 Ti 5 O 12 was significantly lower than that via a standard solid-phase reaction. Huang et al reported a calcination temperature of 9501C for 24 h by applying rutile TiO 2 as the titanium source [16]. High calcination temperature could result in serious sintering of the oxide and also easy evaporation of lithium, which are detrimental to the high-rate performance and should be avoided.…”
Section: Synthesismentioning
confidence: 99%
“…Hence, it is necessary to develop a safer alternative with excellent performance instead of graphite as the negative electrode material. Among those potential candidates, spinel Li 4 Ti 5 O 12 (LTO) is an attractive negative electrode material for lithium ion batteries because of its low cost, environmental friendliness, little irreversible capacity [1], excellent cycling performance with long cycle life [2], and especially higher lithium intercalation potential (about 1.55 V) to avoid the deposition of metallic lithium [3]. Therefore, it is widely used as an anode coupled with high potential cathode materials to replace C/LiCoO 2 cell, such as 2.0 V Li 4 [11,12].…”
Section: Introductionmentioning
confidence: 99%
“…Recently, many researchers [3][4][5][6][7][8][9][10][11][12] reported their study on spinal Li 4 Ti 5 O 12 . They fixed attention on improving the conductivity and electrochemical performance in heavy current.…”
Section: Introductionmentioning
confidence: 99%